Eye and Neck Relaxation Training Using the 20-20-20 Rule to Prevent Computer Vision Syndrome and Text Neck Syndrome Due to Binge- Watching - Lubis, Namora Lumongga; Lubis, Arfah Mardiana; Utama, Surya; Syahri, Isyatun Mardhiyah; Maya Fitria; Asfriyati; Erna Mutiara (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Binge-watching is an activity of watching between two and six episodes of a TV show in one sitting. This activity is mostly carried out by students and teenager. At FKM USU, many students binge-watch, and most of them do it because they want to overcome stress. Binge-watching that is done incorrectly will increase a person's risk of suffer various non-communicable diseases due to reduced activity and snacking while binge-watching. This activity can also increase a person's risk of suffering from Text Neck Syndrome and Computer Vision Syndrome because when someone binge-watches they tend to watch with the wrong posture and are reluctant to stop staring at the screen of an electronic device for hours. Programs or activities must be held within FKM USU to prevent students from suffering from Computer Vision Syndrome and Text Neck Syndrome due to binge-watching. This community service activity was carried out at FKM USU, by giving Eye and Neck Relaxation Training Using the 20-20-20 Rule to 27 participants with lecture and demonstration methods. Participants were also given pre-tests and post-tests and also carried out simulations to assess participants' understanding. Based on the pre-test and post-test results, of the 27 participants, only 19 (70.37%) increased their knowledge. Based on the simulation results, all participants got a score of 100, it can be concluded that the eye and neck relaxation training using the 20-20-20 rule that has been implemented can increase students’ knowledge and skills about the eyes and neck relaxation training using the 20-20-20 rule.